Study of dielectric behavior in PVDF/clay nanocomposites - Chanmal, Chetan; Jog, Jyoti Prakash (E-Polymers, 2009)
A high dielectric permittivity nanocomposite based on poly( vinylidene fluoride) (PVDF) and organically modified clay is reported. The present work aims to study the effect of clay on dielectric behavior of PVDF. The dielectric permittivity study shows a remarkable enhancement in the permittivity of nanocomposites in the low frequency region. The obtained permittivity values fits quite well to the prediction of dielectric permittivity from Vo-Shi model, which takes contribution of interface to permittivity into account. This enhanced permittivity in nanocomposites is attributed to the presence of interfacial polarization. The interface effect is further studied with cole-cole plot analysis. The dielectric loss study of pristine PVDF shows two relaxations associated with segmental (glass transition relaxation) and crystalline chain relaxation. However in the PVDF/Clay nanocomposites crystalline relaxation peak disappears which is attributed to the formation of the beta phase in PVDF/clay nanocomposites.